Description Of Throat Pain In The Use Of LMA And Ett With Post-General Anesthesia Patients - Suyanti, Suyanti; Muhammad Rossy Rachasiwi; Alya Reza Ardhita (Jurnal EduHealth, 2024)
Endotracheal intubation (ETT) involves inserting a tube into the trachea through the mouth or nose with the assistance of a laryngoscope, while the Laryngeal Mask Airway (LMA) is considered a safer supraglottic airway for general anesthesia compared to ETT, which is associated with difficulties in airway management and spontaneous ventilation. A common postoperative complication following both ETT and LMA is sore throat, which can reduce patient comfort after surgery. This study aims to assess the incidence of sore throat in patients after general anesthesia with ETT and LMA, employing a descriptive observational analysis with purposive sampling. The results indicate that the mean sore throat pain scale for LMA is 2.61, while for ETT it is 3.84, indicating that the sore throat pain scale resulting from ETT use is higher compared to LMA use. The findings show that the use of the Laryngeal Mask Airway (LMA) results in a higher pain scale of 2 (23.7%), while the Endotracheal Tube (ETT) has a pain scale of 4 (21.1%). This indicates that LMA is generally more comfortable than ETT, highlighting the importance of effective pain management in clinical practice.